HEALTH OF NEWBORNS BORN OUT OF WEDLOCK - V.К. Yur'ev; N.E. Aref'eva; A.D. Rubin; G.R. G.R. Sagitova ("Paediatrician" Publishers LLC, 2007)
In recent years, both in Russia and most economically developed countries there is a growth of illegitimate births. The birth of a child prior to marriage is usually considered as a risk factor for his health. In Murmansk maternity hospitals, there was an assessment of main health indices of 3 newborns groups: born in registered marriage (114 children), in civil marriage (106 children) and born to unwed mothers (103 children). By questioning mothers, the authors have revealed certain medical and social risk factors for their health. It was established that the health of children born in civil marriage is not worse and according to some indices it is even better than the health of children born in registered marriage. According to most parameters, the health of children born to unwed mothers was certainly worse than the health of the newly born children born to mothers in registered marriage. The differences in indices were due to a larger number of medical and social risk factors, negatively affecting the health of the children born to unwed mothers. Misbegotten children cannot be considered as one group of a social risk. We should only refer children born to unwed mothers to the high risk group, while according to the level of health risk children born in civil marriage are comparable with children born to mothers in registered marriage.Key words: misbegotten children, health of newborns, risk factors.